Minimum Taxes and Repeated Tax Competition - Áron Kiss (Hungarian Academy of Sciences, Institute of Economics, 2011)
An agreement about a lower bound for admissible tax rates can reduce the equilibrium tax rate (and thus welfare) in tax competition among fully symmetric countries. This is shown in an infinitely repeated game where the stage game describes the standard tax competition model with source-based taxes and symmetric countries. Repeated interaction may allow countries to sustain cooperation through implicit contracts. Lower bounds on tax rates ('minimum taxes') restrict the ability of countries to punish deviators. This makes cooperation harder to sustain. The introduction of a lower bound on feasible tax rates may thus harm all countries.
Keywords: F21; H87; 330; tax competition; tax harmonization; minimum tax; tax floor; repeated games; Unternehmensbesteuerung; Steuertarif; Steuerwettbewerb; Steuerharmonisierung; Wiederholte Spiele; Theorie